The effect of perioperative packed red blood cells transfusion on patient outcomes after liver transplant for hepatocellular carcinoma. Issue 3 (March 2022) - Muaddi, Hala; Abreu, Phillipe; Ivanics, Tommy; Claasen, Marco; Yoon, Peter; Gorgen, Andre; Al-Adra, David; Badenoch, Adam; McCluskey, Stuart; Ghanekar, Anand; Reichman, Trevor; Sapisochin, Gonzalo
Abstract: Background: The impact of packed Red Blood Cell (pRBC) transfusion on oncological outcomes after liver transplantation (LT) for Hepatocellular Carcinoma (HCC) remains controversial. We evaluated the impact of pRBC transfusion on HCC recurrence and overall survival (OS) after LT for HCC. Methods: Patients with HCC transplanted between 2000 and 2018 were included and stratified by receipt of pRBC transfusion. Outcomes were HCC recurrence and OS. Propensity score matching was performed to account for confounders. Results: Of the 795 patients, 234 (29.4%) did not receive pRBC transfusion. After matching the 1-, 3-, and 5-year cumulative incidence of recurrence was 6.6%, 12.5% and 14.8% for no-pRBC transfusion, and 8.6%, 18.8% and 21.3% (p = 0.61) for pRBC transfusion. The OS at 1-, 3-, 5-year was 93.0%, 84.6% and 75.8% vs 92.0%, 79.7% and 73.5% (p = 0.83) for no-pRBC transfusion and pRBC transfusion, respectively. There were no differences in recurrence (HR 1.13, 95%CI 0.71–1.78, p = 0.61) or OS (HR 1.04, 95%CI 0.71–1.54, p = 0.83). Conclusion: Perioperative administration of pRBC in liver transplant recipients for HCC resulted in a nonsignificant increase of HCC recurrence and death after accounting for confounder. Surgeons should continue to exercise cation and optimize patients iron stores medically preoperatively.